Awareness, attitude, and prevalence of periodontal diseases in West Godavari District of Andhra Pradesh - Praveen Gadde; Gautami S Penmetsa; M A. K. V Raju; A V. Rama Raju (Wolters Kluwer Medknow Publications, 2019)
Background: Prevention and control of oral diseases, in general, and periodontal diseases, in particular, are influenced by the knowledge attitude and personal behavior of the individual. Aim: The aim of this study was to determine the prevalence of periodontal disease as well as awareness and attitude of the individuals toward periodontal diseases. Material and Methods: This descriptive, cross-sectional epidemiological survey included a total of 3200 individuals with an age range of 18-65 years. For sample selection, West Godavari district was divided into four revenue divisions. From each division, two mandals were selected, and from each mandal, two villages were selected randomly. The examination process included the recording of the indices, namely, Community Periodontal Index (CPI) and Loss of Attachment Index in an attempt to estimate the prevalence of periodontitis. On the other hand, a 23-item questionnaire was given to all the participants involved in the study to assess the knowledge and attitude of the involved individuals. The data collected were analyzed using IBM SPSS version 21.0. Descriptive statistics were computed. T-test and one-way analysis of variance were employed. P < 0.05 was considered statistically significant for all the comparisons. Results: The results of our study showed a prevalence rate of 55.3% in the West Godavari population. Poor knowledge regarding periodontal status was observed in our study in patients above 45 years of age. There was no significant difference in periodontal knowledge score between males and females (P = 0.788). The graduates elicited greater periodontal knowledge compared to illiterates (P < 0.001). Conclusion: Our results showed higher prevalence of periodontal diseases with poor periodontal knowledge score alongside a generally positive attitude toward periodontal health and disease among the West Godavari population. Health education programs should place more emphasis on causes and manifestations of periodontal diseases